Shifting the practice of coercive penal care over time in a problem-solving court - Omori, Marisa (Punishment & society, 2024)
While problem-solving courts represent one area in which rehabilitative efforts have expanded within correctional settings as “coercive penal care,” still unexplored is how the blend of rehabilitative and punitive practices might evolve over time. By conducting interviews and observing a new reentry court, we explore how the court's navigation of coercive penal care transforms over time. We argue that initially, the introduction of rehabilitative goals was mostly subverted by the court's existing punitive criminal legal system and organizational structure. This occurred through court actors prioritizing internal over external goals and metrics in the program, and articulating self-responsibilization narratives for success. As the court progressed, court actors shifted toward emphasizing individualism. Increased individualism occurred in recognition of the complex barriers that participants faced, but presented a double-edged sword: actors focused more on the individual needs of participants beyond program requirements, but also increased individual accountability by participants. This greater emphasis on individualization also allowed court actors to resolve sometimes competing rehabilitative and punitive goals through increased discretion.